DESESTABILIZACIÓN DEL SISTEMA NATURAL A PARTIR DE CAMBIOS EN EL USO DEL SUELO: EL CASO DE LOS DESLIZAMIENTOS DE VISTA ALEGRE, PROVINCIA DEL NEUQUÉN - Elsie M. Jurio; María E. Chiementon; Marcos D. Mare (Boletín Geográfico)
This paper characterizes and analyzes the gravitational movements affecting the edge of the plateau in Vista Alegre, Neuquén Province. A systemic approach to the biophysical environment is applied, from over 20 years of monitoring this phenomenon. Temporal analysis of spatial features is enhanced by the use of remote sensing records and Geographic Information Systems (GIS) processing. The incompatibility between land use (irrigated agriculture on the plateau surface in an semi-arid zone) and its impact on geomorphological processes, results in soil degradation and in the damage of rural works and facilities, defining, in general terms, the current risk situation. The mass wasting processes were triggered by the excessive percolating water supply and currently involve an area of 12 ha. The mudflow lobes extend up to 150 m away from scarp and affect, at their distal section, agriculturally improved land. The total amount of rock and soils collapsed is in the order of 1,160,000 m3. Despite the magnitude of these processes, no action attempting to remediate or resolve the problem has been carried out. Conclusions referred to the study case can be extrapolated, by analogy, to other potentially risky situations, particularly to the urban projects in Neuquén city planned for the plateau surface.